2006
DOI: 10.1093/hmg/ddl410
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal domain of the Aurora-A Phe-31 variant encodes an E3 ubiquitin ligase and mediates ubiquitination of IκBα

Abstract: Aurora-A is an important regulator of mitosis and is frequently amplified in human cancer. Ectopic expression of Aurora-A in mammalian cells induces centrosome amplification, genomic instability and transformation. A common genetic variant in Aurora-A (F31I) is preferentially amplified and is associated with the occurrence and the status of colon, oesophageal and breast cancers. Here we demonstrate that the N-terminal domain of Aurora-A Phe-31 variant exhibits an intrinsic ubiquitin ligase activity. Mutation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In fact, multiple cancer associated mutations in Aurora-A have been identified, of which, some alter the kinase activity and others create or abolish protein interaction (110112). As mentioned earlier, I31F polymorphism in Aurora-A can activate NF-κB pathway through preferential UBE2N interaction to down-regulate I B (28,113). Another V57I polymorphism in Aurora-A shows reduced kinase activity and correlates with aneuploidy.…”
Section: The Future Of Cancer Therapeutics With Aurora Kinase Inhimentioning
confidence: 83%
“…In fact, multiple cancer associated mutations in Aurora-A have been identified, of which, some alter the kinase activity and others create or abolish protein interaction (110112). As mentioned earlier, I31F polymorphism in Aurora-A can activate NF-κB pathway through preferential UBE2N interaction to down-regulate I B (28,113). Another V57I polymorphism in Aurora-A shows reduced kinase activity and correlates with aneuploidy.…”
Section: The Future Of Cancer Therapeutics With Aurora Kinase Inhimentioning
confidence: 83%
“…To confirm the specificity of AKCI for AURKC, we performed in vitro kinase assays using recombinant AURKA, which is known to interact with IκBα [ 21 ]. As shown in Figure 6G , activation of IκBα by AURKA was not altered by AKCI treatment.…”
Section: Resultsmentioning
confidence: 99%
“…A polymorphism in Aurora‐A gene, Phe31Ile has been identified and Aurora‐A Phe31 but not Ile31 has been shown to interact with UBE2N, E2 ubiquitin ligase [Ewart‐Toland et al, 2003]. It has been demonstrated that Aurora‐A Phe 31 not Ile31, in a complex with UBE2N transiently over expressed, has an intrinsic E3 ubiquitin ligase activity and catalyses polyubiquitination of both Aurora‐A itself for protein stabilization and IκBα for protein degradation [Briassouli et al, 2006]. It appears that the previous study utilized Aurora‐A Phe31 isoform, while our study utilized the Ile31 isoform expression construct.…”
Section: Discussionmentioning
confidence: 99%